Teaching Reading Comprehension through Focal Points on R2D2 Model - Yudi Hari Rayanto (Journal of English Language Teaching and Linguistics, 2017)
The purposes of this research are to find out (1) college students’ response during the learning process on Reading comprehension, (2) college students’ learning achievement during the learning process on Reading comprehension. The data are gained from questionnaires and test given to 31 college students in 12 meetings. From 12 meetings, there were two college students did not attend the learning process. And automatically, the researcher only gets 29 questionnaires and answer sheets. All data are analyzed by using descriptive quantitative study. The result shows that college students’ response is categorized high, that is 0,93 (93%) and the result of college student’s learning achievement can be categorized high, all students get more than 90.Keywords: Teaching, Learning, Reading,  R2D2, Focal points